2008
DOI: 10.1007/s11069-008-9310-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in predictability of waves over the Indian Ocean

Abstract: Accurate prediction of ocean surface waves is a challenging task with many associated difficulties. Availability of good quality wind and wave information from satellite platforms inspired the scientific community to assimilate such data in various spectral wave models for enhancing the accuracy of prediction. Over the Indian Ocean, which is the region of interest for the present study, wave heights in extreme situation can go up to 12-14 m, thereby increasing the probability of coastal hazards. This region is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 12 publications
2
8
0
Order By: Relevance
“…(Table 4). The model predicted parameters as shown in Figure 15 reveal good match with the observations as reported by several other researchers such as Raj Kumar et al [13] and Sannasiraj et al [45] in the Indian Ocean. Studies by Raj Kumar et al [13], revealed the model performance to be reasonable during high seastate caused by cyclonic disturbance in the Arabian Sea.…”
Section: Wave Model Validationssupporting
confidence: 83%
See 2 more Smart Citations
“…(Table 4). The model predicted parameters as shown in Figure 15 reveal good match with the observations as reported by several other researchers such as Raj Kumar et al [13] and Sannasiraj et al [45] in the Indian Ocean. Studies by Raj Kumar et al [13], revealed the model performance to be reasonable during high seastate caused by cyclonic disturbance in the Arabian Sea.…”
Section: Wave Model Validationssupporting
confidence: 83%
“…The model predicted parameters as shown in Figure 15 reveal good match with the observations as reported by several other researchers such as Raj Kumar et al [13] and Sannasiraj et al [45] in the Indian Ocean. Studies by Raj Kumar et al [13], revealed the model performance to be reasonable during high seastate caused by cyclonic disturbance in the Arabian Sea. The difference in hindcast and observed Hs mean for October 2000 and the range of Hs for all the buoy locations considered are well within 0.1 m and 0.4 concluded that, the WAM model derived wave parameters such as Hs and Tc compared well with the observed wave parameters in most cases for January 2000.…”
Section: Wave Model Validationssupporting
confidence: 83%
See 1 more Smart Citation
“…A general wave condition in the Arabian Sea during premonsoon and SW monsoon periods also depend on the swells and wind sea identified from the far northwest Arabian Sea because of the northwesterly Shamal winds (Aboobacker et al, 2011a;Glejin et al, 2013). Many authors reported the presence of SW swells (Kumar et al, 2000(Kumar et al, , 2009Kurian et al, 2009) off the west coast of India, but their generating area remain unknown. Hamilton (1992) studied the measured long period waves and low amplitude swells observed from wave buoys deployed in the western North Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The nested boundary condition of time varying two-dimensional wave energy spectra from a coarse resolution (0.25°× 0.25°) SWAN run for the larger Indian Ocean domain is prescribed along the open ocean boundary of the study area. Earlier studies by Raj Kumar et al (2009) and Bhowmick et al (2011) report on the application of SWAN wave model for the Indian Ocean. These studies confine to wave prediction using SWAN in standalone mode.…”
Section: Methodsmentioning
confidence: 99%